Reflective Practice as Spiritual Practice: A Classroom Management Bridging Model for Novice Islamic Religious Education Teachers - Ahmad Maududi; Anisa Dwi Makrufi (Educazione: Journal of Education and Learning, 2026)
Novice Islamic Religious Education (IRE) teachers must manage a classroom effectively while nurturing students' moral and spiritual growth, a dual demand that pre-service training rarely fully prepares them for. When theoretical preparation meets an unpredictable classroom, novice teachers often experience pedagogical shock. Existing reflective practice frameworks explain how teachers work through such shock, yet they rarely examine how religious values shape that process. This study aims to explore the gap between theoretical and practical classroom management among novice teachers, examine the role of reflective practice in narrowing it, and develop a bridging model that integrates reflective practice with Islamic educational values. Using a qualitative case study design, data were gathered through semi-structured interviews and document analysis with four novice teachers. Credibility was secured through source and technique triangulation, and data were analyzed through data condensation, presentation, and conclusion drawing. Findings reveal a persistent theory-practice gap that is addressed through two complementary reflective habits, retrospective evaluation and in-action adjustment, both reinforced by tadabbur, rahmah, adab, muhasabah, and uswah hasanah. These findings extend transformative learning theory beyond its secular foundations. They show that pedagogical shock can trigger not only critical reflection but also a spiritually grounded reworking of professional identity, offering induction programs a model in which reflection functions as both a pedagogical skill and a form of moral formation.